Which health-related quality of life aspects are important to patients with chronic myeloid leukemia receiving targeted therapies and to health care professionals?: GIMEMA and EORTC Quality of Life Group - Efficace, Fabio; Saußele, Susanne; Kossak-Roth, Ute (Annals of hematology, 2012)
The objective of this study was to investigate the health-related quality of life (HRQOL) aspects valued the most by patients with chronic myeloid leukemia (CML) receiving targeted therapies (TT), and to compare their perception with that of health-care professionals’ (HCPs). Semi-structured interviews were conducted with 137 CML patients receiving TT from five different countries. An additional sample of 99 CML patients, completing an online interview, was considered for supportive analyses. A sample of 59 HCPs from 12 countries also participated in the study. Patients and HCPs were asked to rate and rank the importance of a predefined list of 74 HRQOL aspects of potential relevance for CML patients. Patients and HCPs agreed that the following five aspects are most important: fatigue, muscle cramps, swelling, worries, and uncertainty about health condition in the future, and importance of social support in coping with the disease. However, the difference in rankings between the two groups was substantial with respect to other HRQOL aspects investigated. Patients valued some issues related to symptoms much higher than HCPs, thus suggesting that a better symptom management could be the crucial aspects to improve HRQOL of CML patients.
Gesehen am 08.05.2019